2002
DOI: 10.1007/s00024-002-8743-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-range Automaton Models of Earthquakes: Power-law Accelerations, Correlation Evolution, and Mode-switching

Abstract: -We introduce a conceptual model for the in-plane physics of an earthquake fault. The model employs cellular automaton techniques to simulate tectonic loading, earthquake rupture, and strain redistribution. The impact of a hypothetical crustal elastodynamic Green's function is approximated by a long-range strain redistribution law with a r Àp dependance. We investigate the influence of the effective elastodynamic interaction range upon the dynamical behaviour of the model by conducting experiments with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…A strong correlation is evident between the AMR/AER and LURR critical region sizes, suggesting these two observations have a common physical mechanism. Recent simulations demon-strate Accelerating Moment/Energy Release (MORA et al, 2000) and an evolution in stress correlations prior to large events WEATHERLEY et al, 2002) consistent with that predicted by the Critical Point Hypothesis. This suggests a mechanism that is CPH or CPH-like.…”
Section: A Test For a Common Physical Mechanism For Lurr And Amr/aersupporting
confidence: 68%
“…A strong correlation is evident between the AMR/AER and LURR critical region sizes, suggesting these two observations have a common physical mechanism. Recent simulations demon-strate Accelerating Moment/Energy Release (MORA et al, 2000) and an evolution in stress correlations prior to large events WEATHERLEY et al, 2002) consistent with that predicted by the Critical Point Hypothesis. This suggests a mechanism that is CPH or CPH-like.…”
Section: A Test For a Common Physical Mechanism For Lurr And Amr/aersupporting
confidence: 68%
“…In contrast, model F has no systematic dependence of l=r on the fractal dimension D. These observations support our assertion that the distribution type RW is more efficient for tuning the dynamics with a single heterogeneity parameter. ZO¨LLER et al (2004) have shown that high stress fluctuations occurring along cell boundaries on a heterogeneous fault can cause a spontaneous mode-switching between a Gutenberg-Richter and a characteristic earthquake distribution (DAHMEN et al, 1998;BEN-ZION et al, 1999;WEATHERLEY et al, 2002). Although the type of distribution does not change in the simulations leading to Figure 7, the results (especially those for model RW) have time periods with clearly different maximum magnitudes.…”
Section: Analysis Of Earthquake Catalogsmentioning
confidence: 95%
“…Carlson 1991;Rice 1993;Ben-Zion 1996;Langer et al 1996;Fisher et al 1997;Dahmen et al 1998;Lapusta et al 2000;Shaw & Rice 2000;Weatherley et al 2002;Heimpel 2003;Zöller et al 2005;Mehta et al 2006;Hillers et al 2007). Properties such as the energy dissipation and stress interaction distance, dimension, the degree of heterogeneity, and the range of size scales have been used as control parameters.…”
Section: Fault Zone Dynamicsmentioning
confidence: 99%